Using of leaching reactant obtained from mill scale in hydrometallurgical copper extraction - Nizamoglu, Hasan; Turan, Mehmet Deniz (Springer Heidelberg, 2021)
This study, which covered a set of leaching processes at a few stages, investigated the inclusion of iron found in mill scale, which is a waste of the iron-steel industry, in the solution as FeClx=2,3 in the presence of HCl and the conditions of using this solution with an oxidizing character in extraction of metals from chalcopyrite concentrate. Mill scale was treated with HCl, and an FeClx solution was obtained at a 100% Fe solubility and 83.43% Fe3+ conversion rate in the conditions of 60 min, 105 degrees C, 7 M HCl, and 1/10 solid-liquid ratio. This solution that was obtained was later used in copper extraction from a chalcopyrite concentrate. In the optimum conditions (120 min of leaching time, 105 degrees C of leaching temperature, 1/25 solid-liquid ratio, 400 rpm stirring speed), 95.04% of the copper was taken into the solution. In the leaching experiment in a medium containing mill scale + chalcopyrite and HCl at the same time, under the optimum conditions (120 min of leaching time, 105 degrees C of leaching temperature, 7 M HCl concentration, 1 g chalcopyrite concentrate, 1/25 solid-liquid ratio, 5 g mill scale, 400 rpm stirring speed), approximately 96% of copper was taken into the solution.
Keywords: Chalcopyrite; Copper; Hydrometallurgy; Mill scale; Hydrochloric acid; Leaching; Waste